El camino de la comprensión aproximación a una hermenéutica del concepto desde la lectura de G. W. F. Hegel y H.G. Gadamer - Santilli, Oscar Enrique (2005)
Hermeneutics has in “concept" the exercise that updates the correct way of “being" comprehension. From its mythological origin to its location in the ontological sphere, it goes through history together with the advent of thinking into language. In this continuity of sense expressed in the element of dialogue we reach the thought of G.W.F. Hegel and H.G. Gadamer, in which the hermeneutical event discloses its tum from methodological discipline to its ontological-existential installment